2016
DOI: 10.1016/j.renene.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production by Saccharomyces cerevisiae, Pichia stipitis and Zymomonas mobilis from delignified coconut fibre mature and lignin extraction according to biorefinery concept

Abstract: In search to increase the offer of liquid, clean, renewable and sustainable energy in the world energy matrix, the use of lignocellulosic materials (LCMs) for bioethanol production arises as a valuable alternative. The objective of this work was to analyze and compare the performance of Saccharomyces cerevisiae, Pichia stipitis and Zymomonas mobilis in the production of bioethanol from coconut fibre mature (CFM) using different strategies: simultaneous saccharification and fermentation (SSF) and semisimultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Gonçalves et al (2014) showed that a short presaccharification step at 50°C for 8 h in the SSSF process with three microorganisms (S. cerevisiae, P. stipitis, and Z. mobilis) had a positive effect to increase the overall yield of bioethanol from 79.27-84.64% to 85.04-89.15%. In a similar study with coconut fiber, Gonçalves et al (2016) showed the hydrothermal pretreatment catalyzed with NaOH (HPCSH) followed by SSF (SSSF) process using S. cerevisiae, P. stipitis, and Z. mobilis microbes was useful to achieve high yields of bioethanol of 91.17% and 91.03%. Among the existing process of the modified SSF approach, simultaneous saccharification and cofermentation (SSCF) has been most feasible approach to convert both hexose and pentose sugars to increased concentration of lignocellulosic bioethanol.…”
Section: Conventional Fermentation Technology To Produce Bioethanolmentioning
confidence: 99%
“…Gonçalves et al (2014) showed that a short presaccharification step at 50°C for 8 h in the SSSF process with three microorganisms (S. cerevisiae, P. stipitis, and Z. mobilis) had a positive effect to increase the overall yield of bioethanol from 79.27-84.64% to 85.04-89.15%. In a similar study with coconut fiber, Gonçalves et al (2016) showed the hydrothermal pretreatment catalyzed with NaOH (HPCSH) followed by SSF (SSSF) process using S. cerevisiae, P. stipitis, and Z. mobilis microbes was useful to achieve high yields of bioethanol of 91.17% and 91.03%. Among the existing process of the modified SSF approach, simultaneous saccharification and cofermentation (SSCF) has been most feasible approach to convert both hexose and pentose sugars to increased concentration of lignocellulosic bioethanol.…”
Section: Conventional Fermentation Technology To Produce Bioethanolmentioning
confidence: 99%
“…Theoretical solubilized lignin (TSL) was calculated by the Eq. 2, modified from Gonçalves et al [20]:…”
Section: Acid Precipitation Of Insoluble Lignin In the Liquors Obtainmentioning
confidence: 99%
“…cerevisiae was cultivated on agar slant containing 10 g/L glucose, 5 g/L peptone, 3 g/L yeast extract, 20 g/L agar at 28 °C [7]. The inoculum of S. cerevisiae was cultivated on culture medium containing 50 g/L glucose, 1 g/L (NH4)2HPO4, 0.5 g/L KH2PO4, 0.25 g/L MgSO4.7H2O, 10 g/L peptone, 10 g/L yeast extract, at 30 °C for 24 hours [8].…”
Section: Saccharomyces Cerevisiae Preparationsmentioning
confidence: 99%